Assessment of the reliability of deconvolution procedures for RCF spectroscopy of laser-driven ion beams. (1st February 2022) - McCallum, S.; Milluzzo, G.; Borghesi, M.; Subiel, A.; Romano, F.
Abstract: Laser-driven ion beams are defined by a number of unique features, including a large spread in energy. A stack configuration of radiochromic films (RCF) can be utilized to characterize such beams through measurements of their energy spectra. A spectroscopic procedure is reported that allows the proton energy density within each active layer of a radiochromic film (RCF) stack to be retrieved. This is based upon on a deconvolution algorithm developed through Geant4 Monte Carlo simulations to correct the contributions of energy depositions within a given film layer. Through Monte Carlo calculations, the spectrum retrieved from a simulated film stack can be retrieved and compared with a known energy spectrum, providing an examination of the efficacy of this tool. Application of the developed deconvolution procedure thus offers the potential to correctly reconstruct the incident energy spectrum of a laser-driven proton and ion beam from a stack of irradiated RCF.